Extranodal Extension Is a Powerful Prognostic Factor in Bladder Cancer Patients with Lymph Node Metastasis - Fajkovic, Harun; Cha, Eugene K.; Jeldres, Claudio; Robinson, Brian D.; Rink, Michael; Xylinas, Evanguelos; Chromecki, Thomas F.; Breinl, Eckart; Svatek, Robert S.; Donner, Gerhard; Tagawa, Scott T.; Tilki, Derya; et al. (European urology, 2013)
Lymph node metastasis (LNM) is the most powerful pathologic predictor of disease recurrence after radical cystectomy (RC). However, the outcomes of patients with LNM are highly variable. To assess the prognostic value of extranodal extension (ENE) and other lymph node (LN) parameters. A retrospective analysis of 748 patients with urothelial carcinoma of the bladder and LNM treated with RC and lymphadenectomy without neoadjuvant therapy at 10 European and North American centers (median follow-up: 27 mo). All subjects underwent RC and bilateral pelvic lymphadenectomy. Each LNM was microscopically evaluated for the presence of ENE. The number of LNs removed, number of positive LNs, and LN density were recorded and calculated. Univariable and multivariable analyses addressed time to disease recurrence and cancer-specific mortality after RC. A total of 375 patients (50.1%) had ENE. The median number of LNs removed, number of positive LNs, and LN density were 15, 2, and 15, respectively. The rate of ENE increased with advancing pT stage (p<0.001). In multivariable Cox regression analyses that adjusted for the effects of established clinicopathologic features and LN parameters, ENE was associated with disease recurrence (hazard ratio [HR]: 1.89; 95% confidence interval [CI], 1.55–2.31; p<0.001) and cancer-specific mortality (HR: 1.90; 95% CI, 1.52–2.37; p<0.001). The addition of ENE to a multivariable model that included pT stage, tumor grade, age, gender, lymphovascular invasion, surgical margin status, LN density, number of LNs removed, number of positive LNs, and adjuvant chemotherapy improved predictive accuracy for disease recurrence and cancer-specific mortality from 70.3% to 77.8% (p<0.001) and from 71.8% to 77.8% (p=0.007), respectively. The main limitation of the study is its retrospective nature. ENE is an independent predictor of both cancer recurrence and cancer-specific mortality in RC patients with LNM. Knowledge of ENE status could help with patient counseling, clinical decision making regarding inclusion in clinical trials of adjuvant therapy, and tailored follow-up scheduling after RC. Extranodal extension, an independent predictor of both disease recurrence and cancer-specific mortality in radical cystectomy patients with lymph node metastases, improves accuracy of multivariable predictive models. Consideration should be given to standardization of evaluating and reporting extranodal extension.